META-HEURÍSTICA APLICADA AO PLANEJAMENTO DA DESIGNAÇÃO DE MAQUINISTAS A TRENS DE VIAGEM DE LONGA DISTÂNCIA EM FERROVIAS DE CARGA - Gusmao, Kevyn Phillipe (2020)
Among all the modes of transporting goods and people, one of the most important in the whole world is the rail transport. Due to its high capacity to transport goods, in Brazil, its use has been increasing in recent years. For the transportation of these